Письма проф. Е.К. Редина к проф. Н.Ф. Сумцову - Редин, Егор Кузьмич; Редін, Єгор Кузьмич (Х.: Печатное дело, 1909)
About E.K. Redin and the appendix of his letters to professor N.F. Sumcov.
Keywords: Редін Єгор Кузьмич; професор Харківського університету; Professor of Kharkov University; Харківський університет; листи проф. Є.К. Редіна